Influenza and Measles-MMR: two case study of the trend and impact of vaccine-related Twitter posts in Spanish during 2015-2018 - Lucia Prieto Santamaría; Juan Manuel Tuñas; Diego Fernández Peces-Barba; Almudena Jaramillo; Manuel Cotarelo; Ernestina Menasalvas; Antonio Conejo Fernández; Amalia Arce; Angel Gil de Miguel; Alejandro Rodríguez González (Taylor & Francis Group, 2022)
Social media, and in particularly Twitter, can be a resource of enormous value to retrieve information about the opinion of general populaton to vaccines. The increasing popularity of this social media has allowed to use its content to have a clear picture of their users on this topic. In this paper, we perform a study about vaccine-related messages published in Spanish during 2015-2018. More specifically, the paper has focused on two specific diseases: influenza and measles (and MMR as its vaccine). By also including an analysis about the sentiment expressed on the published tweets, we have been able to identify the type of messages that are published on Twitter with respect these two pathologies and their vaccines. Results showed that in contrary on popular opinions, most of the messages published are non-negative. On the other hand, the analysis showed that some messages attracted a huge attention and provoked peaks in the number of published tweets, explaining some changes in the observed trends.